Roles of the genomic sequence surrounding the stem‐loop structure in the junction region including the 3′ terminus of open reading frame 1 in hepatitis E virus replication. Issue 9 (25th May 2018) - Cao, Dianjun; Ni, Yan‐Yan; Walker, Michelle; Huang, Yao‐Wei; Meng, Xiang‐Jin
Abstract : Hepatitis E virus (HEV), a member of the family Hepeviridae, causes both acute and chronic viral hepatitis. We have previously demonstrated that the stem‐loop structure in the junction region (JR) of HEV genome plays a critical role in HEV replication. However, the function of the sequence bordering the JR, including the 3′ terminus of open reading frame (ORF1), in HEV replication is unknown. In this study, a panel of HEV Renilla luciferase (Rluc) replicons containing various deletions at 5′ or 3′ termini of the JR was constructed to determine the effect of the deletions on HEV replication in Huh7 human liver cells. We showed that even a single nucleotide deletion at the 5′ terminus of the JR abolished HEV replication, whereas deletions at the 3′ terminus of the JR also decreased virus replication efficiency. Furthermore, we also constructed firefly luciferase and Rluc dual‐reporter HEV replicons containing the 3′ terminal ORF1 of various lengths and the JR inserted upstream of the Rluc reporter. A higher level of HEV replication was observed in cells transfected with replicons containing the 3′ terminal ORF1 than that of the JR only replicon. We also showed that the ORF3 noncoding sequence along with the JR promoted a higher level of translation activity than that promoted by JR and the ORF2 noncoding sequence. Abstract : A single nucleotide deletion at the 5' terminus of the JR abolished HEV replication, and deletions at the 3' terminus of the JR also decreased virus replication efficiency. A higher level of HEV replication was observed in cells transfected with replicons containing the 3' terminal ORF1 than that of the JR only replicon. The ORF3 noncoding sequence plus the JR promoted a higher level of translation activity than that promoted by JR and ORF2 noncoding sequence.